A comment on the occurrence of gallium and germanium in the Zinkgruvan Zn-Pb-Ag-(Cu) sulphide deposit, Bergslagen, Sweden. (1st October 2016) - Jansson, Nils F.; Malmström, Lars; Zetterqvist, Anders; Allen, Rodney L.
Abstract: The Zinkgruvan deposit has been included in compilations of exceptionally Ga- and Ge-endowed deposits in Sweden. Available published data sets do, however, not support a substantial enrichment in Ga and Ge. In this contribution, we investigate the Ga- and Ge-endowment based on a whole-rock lithogeochemical data and ore grade analyses from the deposit. Based on our results, we find it highly unlikely that a Ga-endowment exists in the ore. A Ge-endowment may exist, but we find no evidence of Ge grades at the 1000 ppm level that have been reported previously.